Use of Machine Perfusion to Increase the Number of Expanded Criteria Deceased Donor Kidney Transplants: A Pharmacoeconomic Analysis - Tedesco Silva, Helio; Ramos, Teresa Raquel De Moraes; De Carvalho, Deise De Boni Monteiro; Ferreira, Gustavo Fernandes; De Andrade, João Marcelo Medeiros; De Andrade, Luis Gustavo Modelli [UNESP]; Abbud-Filho, Mario; Foresto, Renato Demarchi; Manfro, Roberto Ceratti; Esmeraldo, Ronaldo De Matos; Freitas, Tainá Veras De Sandes; Garcia, Valter Duro; et al. (Wolters Kluwer, 2024)
Background. The discard of expanded criteria donor (ECD) kidneys is unacceptably high, considering the growing demand for transplantation. Using machine perfusion may reduce the discard rate, increase the number of transplants, and reduce mortality on the waiting list. Methods. We developed a 5-y Markov model to simulate incorporating the pulsatile perfusion machine into the current government-funded healthcare system. The model compared the universal use of static cold storage for all kidneys with the selective use of machine perfusion for ECD kidneys. Real-life data were used to compose the cohort characteristics in this model. This pharmacoeconomic analysis aimed to determine the cost-effectiveness and budgetary impact of using machine perfusion to preserve ECD kidneys. Results. Compared with the universal use of static cold storage, the use of machine perfusion for ECD kidneys was associated with an increase in the number of kidney transplants (n = 1123), a decrease in the number of patients on the waiting list (n = 815), and decrease in mortality (n = 120), with a cost difference of US dollar 4 486 009 in the period. The budget impact analysis revealed an additional cost of US dollar 4 453 749 >5 y. The budget impact analysis demonstrated a progressive reduction in costs, becoming cost-saving during the last year of the analysis. Conclusions. This stochastic model showed that incorporating machine perfusion for ECD kidneys is most often a dominant or cost-effective technology associated with an increase in the number of transplants and a reduction in the number of patients on the waiting list, reducing mortality on the waiting list.